Plunkett's telecommunications industry almanac 2023 : telecommunications industry market research, statistics, trends and leading companies - Plunkett, Jack W. (Plunkett Research, Limited, 2022)
A complete market research guide to the telecommunications industry--a tool for strategic planning, competitive intelligence, employment searches or financial research. Features our famous trends analysis, technologies, statistical tables and glossary. Includes our profiles of the top 350 telecommunications companies worldwide, public and private, containing addresses, phone numbers and executive names.